A Double-Movement Hermeneutic of Qur’anic Healing Verses and Their Relevance to Anxiety Disorders - Fahimah, Siti; Luthfiyah, Lujeng; Azizah, Shofiqotun (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Studies on the Qur’anic concept of shifāʾ have predominantly emphasized ritual practices and physical healing, leaving its relevance to contemporary psychological disorders—particularly anxiety—largely underexplored. This study re-examines selected shifāʾ verses (Qur’an 9:14–15 and 41:44) through a contextual hermeneutical framework, employing Fazlur Rahman’s double-movement theory to uncover their psychological significance for anxiety management. Adopting a qualitative-descriptive design, the research applies content analysis to reconstruct the historical-moral meanings of the verses and to recontextualize their ethical-spiritual principles within contemporary theories of emotion regulation and cognitive reappraisal. Primary data are drawn from the Qur’anic text and classical as well as modern exegetical works, complemented by contemporary scholarship in Islamic psychology and empirical studies on dhikr and ruqyah practices. The findings indicate that the shifāʾ verses articulate a coherent model of emotional healing, encompassing affective stabilization, spiritual tranquility, psychological resilience, and the release of negative emotional states—dimensions that functionally correspond to core mechanisms of cognitive-behavioral therapy in addressing anxiety. This study proposes an integrative interpretive framework that positions Qur’anic insights as a form of complementary psychospiritual support for mental health, thereby extending the interdisciplinary dialogue between Qur’anic studies, therapeutic practice, and modern psychological approaches.